Análise da eficiência de sequências de pulso de RMN em baixo campo para avaliar qualidade de molhos de tomate comerciais - Moras, Debora Jorge (Universidade Federal de São Carlos, 2023)
Nuclear Magnetic Resonance is a spectroscopic technique based on the interaction of atomic numbers with nuclear spin (l) greater than zero when in the presence of a static magnetic field (B0) and an oscillating magnetic field (B1). This technique is important in many areas of research and development such as organic, inorganic, analytical and physical chemistry, agrochemical production and development. Additionally, it is mostly employed in the pharmaceutical companies, polymer and food industry, in biochemical and biological research and also in the field of chemistry for characterize the chemical composition of samples to be studied, investigate formulations, analyze mixtures, determine purity of compounds and study kinetics and reaction mechanisms, in addition to characterizing molecules. In this work, some works on TD-NMR applied to food analysis are reviewed and an example of the application of this technique is employed to analyze the quality of tomato sauces, using CPMG and CPMG-90 pulse sequences. In the case of tomato sauces, T2 values were related to the amount of water and viscosity, which can be associated to the quality of the product. For some flavors, such as Bolognese type, it is expected to have pieces of meat in its composition and this increases the viscosity, making the sauce thicker and with a lower T2 value. However, given the heterogeneity of this type of sample, it is important to perform a detailed study about other existent T2 components.
The analysis of low field NMR pulse sequences to evaluate the quality of commercial tomato sauces
Keywords: Ressonância Magnética Nuclear; Produtos alimentícios; Tempos de relaxação; CPMG; CPMG-90; molho de tomate; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA